2023
DOI: 10.1088/1741-4326/acb44d
|View full text |Cite
|
Sign up to set email alerts
|

Hot electron and ion spectra on blow-off plasma free target in GXII-LFEX direct fast ignition experiment

Abstract: Polystyrene deuteride shell targets with two holes were imploded by the Gekko XII laser and additionally heated by the LFEX laser in a direct fast ignition experiment. In general, when an ultra-intense laser is injected into a blow-off plasma created by the imploding laser, electrons are generated far from the target core and the energies of electrons increase because the electron acceleration distance has been extended. The blow-off plasma moves not only to the vertical direction but to the lateral direction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In the fast ignition scheme, ultra-intense laser pulses are utilized to generate a relativistic electron beam (REB), injecting into the pre-compressed isochoric plasma. The REB then travels forward as a strong current, heating the high-density fuel to generated a hot spot [4][5][6][7][8]. Research conducted over the past few decades has demonstrated that a guiding cone for heating could enhance efficiency by reducing the distance from the source to the core.…”
Section: Introductionmentioning
confidence: 99%
“…In the fast ignition scheme, ultra-intense laser pulses are utilized to generate a relativistic electron beam (REB), injecting into the pre-compressed isochoric plasma. The REB then travels forward as a strong current, heating the high-density fuel to generated a hot spot [4][5][6][7][8]. Research conducted over the past few decades has demonstrated that a guiding cone for heating could enhance efficiency by reducing the distance from the source to the core.…”
Section: Introductionmentioning
confidence: 99%